2017
DOI: 10.1177/1748895817740173
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing hit-and-run: A study of driver decision-making processes after a road traffic collision

Abstract: Explanations for driver decisions to hit-and-run have largely been based around a rational choiceperspective that suggests drivers consider the expected costs of reporting a collision against the benefits of leaving the scene (see Tay et al., 2008;Fujita et al., 2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The GWR models uncovered that pedestrians/biker-involved crashes were bonded with an even greater likelihood of hit-and-run in the northwestern part (City of Howell) of the study region and the City of Farmington Hills (located at northeast of Detroit). DUI is a societal concern, and this study found that DUI drivers were more likely to hit-and-run, as also revealed by Hopkins et al ( 13 ). GWR models showed that DUI crashes were associated with an even greater hit-and-run likelihood in northwestern part of the study region (from the City of Farmington Hills, Brighton, to Howell).…”
Section: Modeling Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The GWR models uncovered that pedestrians/biker-involved crashes were bonded with an even greater likelihood of hit-and-run in the northwestern part (City of Howell) of the study region and the City of Farmington Hills (located at northeast of Detroit). DUI is a societal concern, and this study found that DUI drivers were more likely to hit-and-run, as also revealed by Hopkins et al ( 13 ). GWR models showed that DUI crashes were associated with an even greater hit-and-run likelihood in northwestern part of the study region (from the City of Farmington Hills, Brighton, to Howell).…”
Section: Modeling Resultssupporting
confidence: 84%
“…From the traditional logit model, crashes that caused higher severities are associated with a lower hit-and-run likelihood. As Hopkins et al ( 13 ) reported, one of the motivations for a driver leaving the scene was based on his or her judgment that the crash was too trivial to report. GWR models uncovered spatially varying associations between crash severity and hit-and-run.…”
Section: Modeling Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, drivers not remaining on the crash scene may simply be looking to buy time to think things through or to “sober up” even when they expect to be eventually caught. For example, Hopkins and Chivers (2019) conducted in‐depth interviews with HR drivers in the United Kingdom to develop a typology of drivers. Although not all HR behaviors seem to be based upon rational decision‐making, Hopkins and Chivers (2019) identified a group of drivers who were “acting rationally in that they were aware that (as a result of drinking) if they reported the collision, they could be prosecuted for drink driving.” If 0.08 BAC laws lead to increased enforcement of traffic laws, this alone could be the reason why some drivers, especially those with prior offenses or suspended licenses, flee the crash scene even without being engaged in impaired driving.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hopkins and Chivers (2019) conducted in‐depth interviews with HR drivers in the United Kingdom to develop a typology of drivers. Although not all HR behaviors seem to be based upon rational decision‐making, Hopkins and Chivers (2019) identified a group of drivers who were “acting rationally in that they were aware that (as a result of drinking) if they reported the collision, they could be prosecuted for drink driving.” If 0.08 BAC laws lead to increased enforcement of traffic laws, this alone could be the reason why some drivers, especially those with prior offenses or suspended licenses, flee the crash scene even without being engaged in impaired driving.…”
Section: Introductionmentioning
confidence: 99%